2019
DOI: 10.1016/j.jcmgh.2018.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Plasticity of Defa4-Expressing Paneth Cells in Response to Notch Activation and Intestinal Injury

Abstract: Background & Aims Loss of leucine-rich repeat-containing G-protein–coupled receptor 5–positive crypt base columnar cells provides permissive conditions for different facultative stem cell populations to dedifferentiate and repopulate the stem cell compartment. In this study, we used a defensin α4-Cre recombinase (Defa4Cre) line to define the potential of Paneth cells to dedifferentiate and contribute to intestinal stem cell (ISC) maintenance during normal homeostasis and after intestinal injury. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 68 publications
1
80
0
Order By: Relevance
“…Recent studies have suggested that activated NOTCH signaling stimulates Paneth cell plasticity during injury-induced regeneration. 42,43 While KLF5 is not expressed in Paneth cells during homeostasis, the majority of cells within regenerative crypts express KLF5, indicating that KLF5 remains a critical player in the regenerative response. Furthermore, this response may be facilitated via KLF5-mediated NOTCH signaling regulation in other precursors.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that activated NOTCH signaling stimulates Paneth cell plasticity during injury-induced regeneration. 42,43 While KLF5 is not expressed in Paneth cells during homeostasis, the majority of cells within regenerative crypts express KLF5, indicating that KLF5 remains a critical player in the regenerative response. Furthermore, this response may be facilitated via KLF5-mediated NOTCH signaling regulation in other precursors.…”
Section: Discussionmentioning
confidence: 99%
“…Both LGR5 + and Bmi1 + cells can generate intestinal organoids in culture (113). After ablation of LGR5 + cells, Bmi1 + cells can restore the crypt base cell population, providing evidence for significant plasticity of cell identities in the crypt (15), a concept that has been supported by findings that the crypt base can be repopulated by other cell types as well, including differentiated endocrine and Paneth cells (15,16,107,(114)(115)(116)(117). A recent study has also proposed the presence of a distinct revival stem cell population that can repopulate the crypt in conditions of severe damage (118).…”
Section: Mammalian Intestinal Stem Cellsmentioning
confidence: 95%
“…In ex vivo study, the plasticity of PCs can be increased, under the Notch pathway was actively or passively activated condition. In vivo studies, Notch target genes, such as Notch intracellular domain (NICD) and Hes1, were activated in the small intestinal PCs of irradiated mice [33]. Forced NICD expression in PCs leads to transient proliferation states, followed by differentiation into other types of intestinal epithelial cells [33,35].…”
Section: Contribution Of Paneth Cells To Intestinal Epithelium Renewalmentioning
confidence: 99%